Termite communication during different behavioral activities - Costa-Leonardo, Ana Maria [UNESP]; Haifig, Ives [UNESP] (Springer Nature, 2014)
This chapter reviews the communication that occurs among termites performing different behavioral activities. Termites are social insects, and social activities require communication signals that are emitted by signaler individuals and perceived by receiver individuals. Termite castes are mostly blind, and the communication among individuals occurs predominantly through chemical and mechanical cues. The chemical communication involves pheromones that elicit behavioral responses from the individuals; these semiochemicals signal the trail from the nest to food, the presence of enemies, the location of reproductive partners and provide cues for the recognition of nestmates. In addition, indirect communication occurs during building activities through a self-organized mechanism in which the information that elicits termite behavior comes from changes in the environment and does not require direct contact among individuals.